On completeness of the set of root vectors for unbounded operators - Gorbachuk, V. I.; Gorbachuk, M. L. (Methods of Functional Analysis and Topology, 2006)
For a closed linear operator A in a Banach space, the notion of a vector accessible in the resolvent sense at infinity is introduced. It is shown that the set of such vectors coincides with the space of exponential type entire vectors of this operator and the linear span of root vectors if, in addition, the resolvent of A is meromorphic. In the latter case, the completeness criteria for the set of root vectors are given in terms of behavior of the resolvent at infinity.